All-Russian Voting as an Institution of Democracy: Justification, Effects, Perspectives - I. V. Ignatushko (Дискурс)
Introduction. The actuality of the topic is determined by the emergence of a new institution for Russia – the all-Russian voting, regarding which there is no single interpretation of the scientific community. The reform of the Constitution – amendments in 2020 – solved the urgent questions concerning the value-ideological sphere and also the socio-economic and political ones. The purpose of the article is to determine the justification, effects and perspectives of all-Russian voting as an institution of democracy and a legal institution. We made an attempt to systematically analyze the phenomenon of all-Russian voting and determine its meaning and prospects on the basis of existing regulatory legal acts, scientific developments of sociologists and lawyers. It provides the novelty of the work presented.Methodology and sources. The empirical base of the study is the data of the All-Russian Public Opinion Research Center poll on the awareness of Russians about the nationwide voting on amendments to the Constitution, as well as the results of the All-Russian Public Opinion Research Center electoral forecast on 06.23.2020, materials of the official website of the Central Election Commission of the Russian Federation on the results of the all-Russian vote in 2020. In our work we used the concepts and developments of Russian scientists: Dzidoev R. M., Ilyin V. A., Morev M. V., Khorunzhiy S. N., Khristoforova E. I., Sokolova E. A., Chebotarev G. N. and others. We also used M. Weber’s theory of plebiscite democracy and the theory of social institution. The study used the method of systems analysis and general logical methods.Results and discussion. In connection with the conduct of the all-Russian vote on the approval of amendments to the Constitution of the Russian Federation in 2020, new regulatory legal acts were adopted. The emergence of the phenomenon of all-Russian voting has caused discussions in the scientific community and in society about the legitimacy and consequences of this political and legal phenomenon. In the article the author examines the sociological aspects of the all-Russian vote as an institution of democracy regarding the validity, nature, causes, consequences and perspectives. Namely, the forecasts of the institutionalization of the all-Russian vote, the features of this manifestation of democracy in relation to other forms of democracy in Russia, its significance for society are touched upon.Conclusion. Russia is a democratic state, and the forms of manifestation of democracy are enshrined in legislation. The all-Russian voting was held in accordance with the regulatory legal acts specially created for its implementation. A new institution of democracy has been formed. The result of voting for amendments to the Constitution showed the level and dynamics of interaction between the state and society, the timeliness of the questions put to the voting. Withal, the introduction of the all-Russian voting in the legal system of Russia and the question of the final institutionalization of the relevant relationship seems unlikely.